If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 5) + -1(y + 4) = 8 Reorder the terms: 2(5 + y) + -1(y + 4) = 8 (5 * 2 + y * 2) + -1(y + 4) = 8 (10 + 2y) + -1(y + 4) = 8 Reorder the terms: 10 + 2y + -1(4 + y) = 8 10 + 2y + (4 * -1 + y * -1) = 8 10 + 2y + (-4 + -1y) = 8 Reorder the terms: 10 + -4 + 2y + -1y = 8 Combine like terms: 10 + -4 = 6 6 + 2y + -1y = 8 Combine like terms: 2y + -1y = 1y 6 + 1y = 8 Solving 6 + 1y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 1y = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 1y = 8 + -6 1y = 8 + -6 Combine like terms: 8 + -6 = 2 1y = 2 Divide each side by '1'. y = 2 Simplifying y = 2
| 5(x+2)-3(x+1)=9 | | 2-4x=1-5x | | 5-3t=7-t | | 5x+12=-27+8x | | 3+2x=18-3x | | 10-2x=4+x | | 3a-1=7a-9 | | 3x+12=58-2x | | 9a=a+16 | | 5x-4y=19y | | k(x^2-3x+4)+x-3=0 | | f(4x^2+3)=0 | | k^2-k-2=0 | | 7(5-x)=14 | | k^3-k^2-2k-12=0 | | (x-3)(x^3-1)=0 | | x^8=-1 | | 111-5x=13x+23 | | 147-6x=21x+21 | | 4(h*h)+5h=84 | | 6z-12=5 | | 10x-22+5x=3 | | (78).425= | | 5x=3x^2 | | (5x+3)*(24-3x)=0 | | x^2+21x+32=12 | | 8x-8=x+7 | | b=(11b+14)(8-10b) | | 5x+8=3(x+4) | | b=8a(8A-13) | | 8p+p^2=105 | | 8x+19=2x+163 |